Superlubricity induced by partially oxidized black phosphorus on engineering steel - Kai Gao; Jianguo Jiao; Zheng Wang; Guoxin Xie; Jianbin Luo (Friction)
Abstract Macroscale superlubricity has attracted increasing attention owing to its high significance in engineering and economics. We report the superlubricity of engineering materials by the addition of partially oxidized black phosphorus (oBP) in an oleic acid (OA) oil environment. The phosphorus oxides produced by active oxidation exhibit lower friction and quick deposition performance compared to BP particles. The H-bond (-COOH⋯O-P, or -COOH⋯O=P) formed between P-O bond (or P=O) and OA molecule could benefit the lubricating state and decrease the possibility of direct contact between rough peaks. The analysis of the worn surface indicates that a three-layer tribofilm consisting of amorphous carbon, BP crystal, and phosphorus oxide forms during the friction, which replaces the shear interface from the steel/steel to carbon—oBP/carbon—oBP layer and enables macroscale superlubricity.